Challenges and Coping Strategies of Intermediate Teachers in Handling Generation Z Learners - Dejacto, Ladylou; Valmorida, Francis May; Naparan, Genesis (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
The learners as of the present are called Generation Z learners. This study aimed to come up with the common challenges and coping strategies of teachers in handling Generation Z learners in the intermediate level. The study was conducted during the school year 2019-2020. The participants were the intermediate teachers in District 10 of Ozamiz City Division. This study employed a phenomenological qualitative research design. The focus of this study was to gather the common challenges and coping strategies of teachers based on their experiences. The responses were analyzed through the use of thematic analysis. It was found out that the challenges commonly met by the intermediate teachers were learners’ difficult behaviors, negative impact of technology/inappropriate use of technology and poor academic performance. The study also revealed that the coping strategies of the teachers were ICT integration in teaching, imposing friendly classroom discipline, parent-teacher partnership, and enhancing teachers’ ICT literacy. This study suggested that in planning teachers’ training programs, administrators of the Department of Education should also include topics that focuses on how to cope up teachers’ challenges met in their classrooms. Topics may involve handling Generation Z learners and developing necessary skills in innovative teaching.